IMPLEMENTASI KONSEP JURAN TRILOGY DALAM PENINGKATAN MUTU PENDIDIKAN - Zen, Ahmad Raihan; Sohiron, Sohiron (Jurnal Manajemen Pendidikan, 2026)
The improvement of educational quality has become a strategic necessity in facing global challenges. Therefore, an effective management framework such as the Juran Trilogy, which includes quality planning, quality control, and quality improvement, is essential. This study aims to examine the implementation of the Juran Trilogy concept in enhancing educational quality by utilizing secondary data obtained from various scientific articles and previous research findings. The research employs a qualitative descriptive method, involving document review and content analysis of scholarly publications that discuss the application of the Juran Trilogy concept within the educational context. The collected data were analyzed thematically to identify patterns, tendencies, and conceptual meanings related to the implementation of the Juran Trilogy in educational quality management practices. The results indicate that the consistent application of the Juran Trilogy concept has a positive impact on improving educational quality, particularly in aspects of planning, process control, and continuous improvement, although challenges remain in maintaining its consistent implementation in practice.